The effect of price, comfort, and trust upon the decision to buy at the online shop (Case study on the students at Economic College of Binaniaga) - Adri Wihananto (STIE Binaniaga, 2020)
This research aims to find out the effects of the price, comfort, and trust simultaneously upon the decision to buy online, (Case study on the students of STIE Bina Niaga Bogor). Techniques of Analysis has applied multiple linear regression analysis to show the extent of which the price, comfort and trust either partially or simultaneously have affected the decision to buy online. Simultaneous result indicated that the effects of the price, comfort, trust either partially and simultaneously had affected the decision to buy online. This result is indicated by the value of Fcount of 40.938. However, Ftable df: α, (k-1), (n-k) = 0.05, (2-1), (151-3) is 4.60. Therefore the calculation of Fcount > Ftable (40.938 > 4,60) at sig. value of 0.000 < 5% (0.05). Keywords: Price, Confort, Trust, Decision to Buy Online.